1959
DOI: 10.2136/sssaj1959.03615995002300030014x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Hydrolyzed Polyacrylonitrile on Kaolinite: II. Effect of Solution Electrolytes

Abstract: Adsorption experiments were conducted by mixing NaCl‐kaolinite and C14‐labelled hydrolyzed polyacrylonitrile (HPAN) in water solutions of various electrolytes. An increase in the concentration of electrolyte caused an increase in extent of HPAN adsorption, the effect apparently being due to reduction of electrostatic repulsion between HPAN and kaolinite and reduction in size of the HPAN coil. Divalent cations, especially the transition metals capable of being complexed, were more effective than univalent catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Further increase in ionic strength from 50 to 200 mol/m 3 had little effect on the PSS adsorption. Similar observations of the influences of pH and ionic strength on the adsorption of charged polymers were reported by Mortensen (1959) and Parfitt (1972).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Further increase in ionic strength from 50 to 200 mol/m 3 had little effect on the PSS adsorption. Similar observations of the influences of pH and ionic strength on the adsorption of charged polymers were reported by Mortensen (1959) and Parfitt (1972).…”
supporting
confidence: 87%
“…According to Sposito (1989), the thickness of the diffuse double layer on montmorillonire decreases from 30 to 3 nm when the ionic strength increases from 0.1 to 10.3 mol/m 3. Ruehrwein and Ward ( 1952) and Mortensen (1959) also suggested that electrolyte was necessary to reduce the electrostatic repulsion between the anionic polymer and the clay particles. Furthermore, studies have shown that solution ionic strength affects the charge and configuration of polymer coil (Markovitz and Kimball, 1950).…”
Section: Influences Of Ph and Ionic Strength On Pss Adsorptionmentioning
confidence: 99%
“…Appreciable uptake, however, can take place under acid conditions and/or at high ionic strength when the negative charge on the polyanion becomes effectively neutralized by protonation and/or is screened by the electrolyte. Adsorption is also promoted by the presence of polyvalent cations which act as "bridges" between the anionic groups on the polymer and the negatively charged sites on the clay, as illustrated by the work of Mortensen (1962) (Figure 4). At acid pH, polyanions also adsorb onto the clay crystal edges by electrostatic interactions ("anion exchange") because aluminum exposed at these sites acquires a positive charge.…”
Section: Aspects Of Polymer Adsorptionmentioning
confidence: 99%
“…Electrostatic attraction to positive charges at crystal edges, precipitation and coordination involving multivalent exchangeable cations and hydrogen bonding between the carboxyl groups of the polyanion and the oxygens of the clay lattice, have been invoked as bonding mechanisms (Ruehrwein and Ward, 1952;Michaels, 1954;Emerson, 1956Emerson, , 1960Packter, 1957;Warkentin and Miller, 1958;van der Watt and Bodman, 1960). Under the conditions of maximum chain extension and hence optimum flocculating eff• ciency, however, the polyanion is largely repelled by the negatively charged clay surfaces unless the zeta potential is lowered by addition of electrolytes (Ruehrwein and Ward, 1952;Mortensen, 1960). The number of polyanion segments involved in interparticle bonding is therefore not likely to be large.…”
Section: Effect Of Clay-polymer Interactions On Soil~clay Propertiesmentioning
confidence: 99%